Characterization of the endosperm starch and the pleiotropic effects of biosynthetic enzymes on their properties in novel mutant rice lines with high resistant starch and amylose content - Itoh, Yuuki (Plant science : an international journal of experimental plant biology, 2017)
Copyright © 2017 Elsevier B.V. All rights reserved.